Digital twin: history of origin and development prospects - D. A. Sosfenov (Интеллект. Инновации. Инвестиции, 2023)
In the modern world, with the advent of the fourth industrial revolution, enterprises are striving to increase the level of efficiency of their activities through the introduction of new generation information technologies that are actively gaining popularity. The use of such technologies allows companies to increase the efficiency of production and management processes. A digital twin is a virtual model of a physical object that helps high-tech enterprises enter a new stage of technological development and increase their competitiveness in the market. The article discusses the stages of development of this technology, starting from the moment the concept was born as an idea, and up to its application in various industries at the present time.